ON ξ-CONFORMALLY FLAT TRANS-SASAKIAN MANIFOLDS ADMITTING SEMI-SYMMETRIC NON-METRIC CONNECTION - Abhishek Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We studied a conformally flat trans-Sasakian manifold admitting a semi-symmetric non-metric connection. Some interesting results on a Kenmotsu manifold admitting the semi-symmetric non-metric connection concluded as well